Cuba, the economic and social revolution - Seers, Dudley (Westport, Conn. : Greenwood Press, 1975)
This is study of economic and social developments in Cuba since the Revolution which assessed the changes that have occurred since the Castro government came to power in 1959, and attempt to foresee what lies in store for the country in the critical years ahead.
Reprint of the ed. published by the University of North Carolina Press, Chapel Hill.
Includes bibliographical references and index.
lje 23/10/18
Loans
Keywords: Economic development; Economic growth; Economic development-Cuba; Cuba